Ответы и объяснения

ILALIG
ILALIG

10*(m+5)+2*(-2m+3n)=10m+50-4m+6n=6m+6n+50
7x*(4y-x)+4x*(x-7y)=28xy-7(x)^2+4(x)^2-28xy=-3(x)^2
4a*(7x-1)-7*(4ax+1)=28ax-4a-28ax-7=-4a-7
a*(a+b)+b*(a-b)=(a)^2+ab+ab-(b)^2=(a)^2+2ab-(b)^2
2(a)^2-a*(2a-5b)-b*(2a-b)=2(a)^2-2(a)^2+5ab-2ab+(b)^2=3ab+(b)^2
5a*(6a+3b)-6a*(5b-2a)=30(a)^2+15ab-30ab+12(a)^2=42(a)^2-15ab
8m*(m+n)-3n*(2m-4n)=8(m)^2+8mn-6mn+12(n)^2=8(m)^2+2mn+12(n)^2

0.0
0 оценок
0 оценок
Оцени!
Оцени!
что значит the
ой tex
ILALIG
Вы с мобильной версии?
ILALIG
Так понятно?
да